EXPLORING GENDER ROLES AND PATRIARCHY IN "THE STORY OF AN HOUR" BY KATE CHOPIN: A FEMINIST ANALYSIS - Mrs Nadia Sheheryar (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper is a feministic interpretation of the Kate Chopin’s “The Story of an Hour”. This research falls under the category of qualitative descriptive study. This paper employs Judith Butler’s theories on gender roles and patriarchy as the theoretical framework. The paper focuses on the societal expectations of women of the late nineteenth century by analyzing the character of Mrs. Mallard and her emotional evolution after the news of her husband’s death. In this paper, Chopin’s narrative will be analyzed on the basis of Butler’s gender performativity and subversiveness to patriarchal norms. This paper affirms that the story presents the brief experience of personal liberty as a sad commentary on the oppression of women. By reading Chopin’s texts through the lens of Butler’s theories, this study advances the field of feminist literary criticism.